Partisipasi Mahasiswa KKN UNP dalam Membantu Proses Belajar Mengajar di SDN 08 Nagari Indudur - Leni Zahara; Indah Maharani Fortuna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Educational resource limitations in remote areas pose a crucial challenge to equitable education quality in Indonesia. This research examines the vital role of "Kuliah Kerja Nyata" (KKN) students (community service program) in addressing these issues, particularly at SD 08 Indudur, Koto IX Sungai Lasi District, Solok Regency. Through a participatory approach and in-depth observation, this study reveals how KKN students not only serve as substitute teachers but also as agents of change who inspire students, increase learning motivation, and help develop a more conducive learning environment. These findings underscore the immense potential of the KKN program as an innovative solution to improve education quality in areas in need, while also providing valuable experience for students in developing self-competence and a sense of social awareness. This research recommends the need to strengthen synergy between universities, local governments, and communities in designing and implementing more effective and sustainable KKN programs.